Las adaptaciones literarias a novela gráfica como recurso didáctico: propuesta para un análisis cualitativo - Moya García, María; Capperucci, Davide (Studi sulla Formazione/Open Journal of Education, 2023)
The aim of this paper is to study literary adaptations of classic works to the graphic novel. In addition, a number of criteria are set to determine the validity and suitability of a specific work as a didactic resource. First, we start from the success of the genre in recent years, both among the general public and in the educational sphere. Second, we offer an overview of the adaptations of classics into graphic novels and their relevance in the classroom. Finally, we present a list of criteria for an objective and exhaustive analysis of each of the works. The purpose is to offer the educational community a practical tool to analyze and qualitatively evaluate a given work before proceeding to carry out a project.